TYPES OF SHELLFISH (BIVALVES) IN THE SIRUSO ISLAND WATER AREA, SIKAKAP DISTRICT, MENTAWAI REGENCY - Febriweni, Nia (BioCONCETTA, 2023)
Siruso Island is part of Taikako Village, Sikakap District, Mentawai Islands Regency. Siruso Island will be used as a tourist object. Tourist destinations can disturb the diversity of living things, one of which is Bivalvia (clams) on this island. This sampling aims to determine the types of clams (Bivalvia) on Siruso Island. This sampling was carried out in August 2022. This sampling is included in a descriptive survey research using the cruising method using the hand shorting technique. The sampling process was carried out at low tide to obtain data. The samples taken were samples that were still alive or samples that were dead or sample shells, with the criteria of intact or unbroken shells and good color. Sample identification was carried out at the Zoology Laboratories of PGRI University, West Sumatra. The results showed that the Bivalve obtained consisted of 4 Orders, 9 Families and 22 Species.